2D multichannel seismic reflection processed data (GI Gun entire dataset) of RV METEOR during cruise M154/1 - Michel Kühn; Christian Berndt; Sebastian Krastel (PANGAEA, 2023)
This 2D multi-channel seismic dataset was acquired during METEOR cruise M154-1 offshore Montserrat in April 2019. The dataset contains ~600 km of normal-moveout-corrected, stacked and migrated vertical seismic profiles. Aim of the seismic experiment was to map and image landslide deposits offshore Montserrat. The data was collected with a 81 m to 152 m-long (16 to 65 channels) streamer system with a group spacing of 1.56 m. The system consisted of two to seven 12.5 m-long active sections, a 25 m-long vibro-stretch section and a 31 to 40 m-long tow cable. As seismic source, two GI airguns (105/105 cubic inch) were shot every five seconds. Seismic data processing included trace editing, highpass filtering (25 Hz cut and 55 Hz slope corner frequencies), denoising, deconvolution, normal moveout correction, stacking and finite-difference migration with a gradient velocity model (1580 m/s to 1725 m/s). Detailed information on the data acquisition can be found in the M154-1 cruise report (https://doi.org/10.2312/cr_m154_1).